Morphological Characterizations of Selected Brown Rice Commercially Available in East Coast of Peninsular Malaysia - Wan Rosli, W. I.; Nurul Ain, I (Microscopy Society of Singapore, 2014)
Presently, the intake of brown rice becomes more popular for people who are very conscious about their health. The present study was conducted to examine the morphological characteristics of different sources of brown rice commercially available in Kelantan state of Peninsular Malaysia. Macroscopic observation was done on fresh brown samples and white rice sample. Longitudinal and horizontal section shows the present of both aleuron and bran layers obviously for all brown rice samples. Long grain and wholegrain mix brown rice had the longest and the thickest values compared to control (white rice). The brown rice samples consist of the pericarp, aleuron layer, endosperm, starch, parenchyma cells and parenchyma cells wall. All brown rice samples also had different thickness of aleuron layer. The cross sectional diameters of the brown rice samples were in the range from 847.2 to 1000 μm. These observations are vital in choosing the best cooking techniques for brown rice that give palatable for human consumption.